Quantification of soil inorganic carbon using sulfamic acid and gas chromatography - Christopher Yip; Philip D. Weyman; Kimberly A. Wemmer; Yun-Ya Yang; Anupam Chowdhury; Bjorn A. Traag; Tania Timmermann; Gonzalo Fuenzalida-Meriz (PLoS ONE, 2025)
Carbon dioxide is the primary greenhouse gas emitted through human activities, and these emissions impact the carbon cycle for hundreds to thousands of years. As carbon dioxide removal strategies to address this challenge continue to be explored and scaled, faster methodologies with high accuracy and precision are required to support the carbon measurements on which these strategies hinge. Of the many available methods to measure soil inorganic carbon, only a select few satisfy all the following criteria: measure inorganic carbon directly, use standardized equipment, perform the measurement automatically, and operate at high throughput. In this work we present a robust protocol for the sensitive and specific quantification of inorganic carbon from soils using gas chromatography to quantify carbon dioxide evolved from carbonates in soil with sulfamic acid. We demonstrate the precision of this method with purified carbonates, carbonate minerals, biogenic carbonates, and agricultural soil samples. We also demonstrate the accuracy of this method by adding known amounts of calcium carbonate to a variety of soil matrices. We find that sulfamic acid is well suited for carbonate dissolution and is compatible with gas chromatography applications, and we note that the method generates results that are equivalent to the typical methods used in this field. This method is compatible with automation and operation at a greater scale and enables the creation of higher resolution soil inorganic carbon datasets.